"Tiny Wiggles" in the Late Miocene Red Clay Deposits in the North‐East of the Tibetan Plateau. Issue 16 (21st August 2021) - Zhang, Rui; Wei, Xiaohao; Kravchinsky, Vadim A.; Yue, Leping; Zheng, Yan; Qin, Jie; Yang, Lijun; Ma, Minghao; Xian, Feng; Gong, Hujun; Zhang, Yunxiang; Liu, Xiaofan
Abstract: Small amplitude or short period geomagnetic anomalies known as "tiny wiggles" (TWs) are often hard to identify because of magnetic signal smoothing in the marine record of geomagnetic reversals. We report here the late Miocene record of geomagnetic reversals in the aeolian red clay sediments of Linxia Basin in China that enables us to identify two TWs. We performed magnetostratigraphy dating and used spectral analysis to distinguish orbital cycles in the records of magnetic susceptibility (MS) and sedimentary grain size (GS) and develop an orbitally tuned age model. The presence of two TWs in the study section, that correspond to C5n.2n‐3 and C5r.2r‐1, is confirmed by orbital calibration of our age model through recognition of eccentricity, obliquity and precession in MS and GS records. Plain Language Summary: Two notable Miocene geomagnetic events are extensively discussed in the literature—the C5n.2n‐3 and C5r.2r‐1. However, they are seldom reported in the continental records, especially discussed in the stable aeolian sediments which has more than 20 Myr long geological history. Here, we report our accurately dated climate proxy record of magnetic parameters from the Linxia red clay section near the Tibetan Plateau. It demonstrates that such short geomagnetic reversals which we identified in the red clay after confirmed the possible magnetostratigraphic and biotratigraphic model by cyclostratigraphy. The magnetic susceptibility and grain size record, indicators of paleosummer and winter monsoon intensification, exhibited variations linked to eccentricity cycles as well as obliquity and precessions in the atmospheric air circulation pattern. The dating coincided with changes in the marine records. Therefore, we discuss the possibility that the two tiny wiggles were related to abrupt changes of full (true) polarity reversal patterns of the Earth's interior. Key Points: Astronomical calibration confirmed a magnetostratigraphic model of red clay across C5n.2n to C5r.2r in the NTP All Milankovitch cycles were found through the wavelet spectral analyses It demonstrates existence of two tiny wiggles and the duration were estimated by orbital cycles